Evaluation of the Implementation of Tourism Policy - Yerik Afrianto Singgalen; Pamerdi Giri Wiloso; Gatot Sasongko (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2017)
This purpose of the study is to  evaluate the  implementation of tourism programs in Bobale Island, Kakara Island, Tagalaya Island and Meti Island in North Halmahera District. The study is based on a model developed by George Edward III, and used qualitative methods to collect and analyze data.  Data collection techniques used included in-depth interviews, observation and study of the documents. Results of the study showed that resources, communication, disposition and bureaucratic structure are the main factors that influence the implementation of tourism policies are. Nonetheless, this study also showed that public support through public participation in the implementation process is also an important factor that determines the success of tourism policy. To that end,   community support or community participation should be an important factor that must be taken into account in the formulation of development priorities of Tourism development Master plan for North Halmahera District government.